Further studies on the photoreactivities of ruthenium–nitrosyl complexes with terpyridyl ligands. (1st July 2019) - Sasaki, Isabelle; Amabilino, Silvia; Mallet-Ladeira, Sonia; Tassé, Marine; Sournia-Saquet, Alix; Lacroix, Pascal G.; Malfant, Isabelle
Abstract : Exposure of the ruthenium terpyridyl complex to NO gas leads to the ruthenium–NO complex with nitrosation of the ligand. Abstract : This study focuses on the two cis / trans -(Cl, Cl)-[Ru(R-Phtpy)Cl2 (NO)] + isomers, where the R group is a NEt2 substituent on the 4′-position of the phenylterpyridine (Phtpy) moiety. The photophysical characteristic properties of the two isomers and those of one nitrosamine derivative are described. The NO release properties are evaluated and show that the cis isomer is the most efficient with a good quantum yield of NO release. The X-ray structures of three ruthenium–nitrosyl complexes and of a photoproduct are presented.